Sex differences in mental strategies for single-digit addition in the first years of school. Issue 1 (2nd January 2020) - Sunde, Pernille B.; Sunde, Peter; Sayers, Judy
Abstract: Strategy use in single-digit addition is an indicator of young children's numeracy comprehension. We investigated Danish primary students' use of strategies in single-digit addition with interview-based assessment of how they solved 36 specific single-digit addition problems, categorised as either 'error', 'counting', 'direct retrieval' or 'derived facts'. The proportional use of each strategy was analysed as multi-level functions of school age and sex. In a first study (260 interviews, 147 students) we found decreasing use of counting and increasing use of direct retrieval and derived facts through years 1–4, girls using counting substantially more and the other two strategies substantially less than boys, equal to more than 2 years' development. Similar results appeared in a subsequent study (155 interviews, 83 students), suggesting that the pattern is pervasive in Danish primary schools. Finally, we ask whether sex differences in strategy use is generally under-reported since many studies do not explicitly address them.